Motivasi Berhubungan dengan Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Tambah Darah: Studi di Puskesmas Johar Baru, Jakarta Pusat - Utami, Lucia; Hia, Wan April Suffer Happy (Kisi Berkelanjutan: Sains Medis dan Kesehatan, 2025)
Introduction and Methods Iron deficiency anemia in pregnant women can contribute to high maternal and infant mortality rates. The high prevalence of anemia among pregnant women may be influenced by their motivation and adherence to consuming iron supplements. This study aimed to analyze the relationship between motivation and adherence in consuming iron tablets among pregnant women at Johar Baru Health Center, Central Jakarta. A descriptive correlational quantitative design was used with a cross-sectional approach. Data collected through questionnaires and analyzed using univariate and bivariate analysis. The Kendall’s Tau B statistical test was employed. The sample size was determined using the Slovin formula, resulting in 52 respondents. Results The univariate analysis showed the following respondent characteristics: aged 20–35 years (90.4%), high school to college education level (84.6%), in the second and third trimesters of pregnancy (100%), and multigravida (63.5%). Most respondents had high motivation to consume iron supplements (71.2%) and a good level of adherence (67.3%). The Kendall’s Tau B test showed a p-value < 0.05, indicating a significant relationship between motivation and adherence to iron tablet consumption among pregnant women. Conclusion and Recommendation Motivation plays a crucial role in improving adherence to iron tablet consumption among pregnant women. It is recommended to provide continuous education about the importance of iron supplementation during pregnancy. Contribution to the Sustainable Development Goals (SDGs) This study aims to explore the factors associated with iron tablet consumption among pregnant women. The article contributes to the third SDG goal: ensuring healthy lives and promoting well-being for all ages. Specifically, it supports target 3.1: by 2030, reduce the global maternal mortality ratio to less than 70 per 100,000 live births.